Attributable cost and extra length of stay of surgical site infection at a Ghanaian teaching hospital. Issue 2 (June 2020) - Fenny, Ama Pokuaa; Asante, Felix Ankomah; Otieku, Evans; Bediako-Bowan, Antionette; Enemark, Ulrika
Abstract: Background: Limited information is available on the financial impact of healthcare associated infections in Sub-Saharan Africa. A prospective case-control study was undertaken at Korle-Bu Teaching Hospital, Ghana, to calculate the cost of surgical site infections (SSI). Methods: We studied 446 adults undergoing surgery from the surgical department. In all, 40 patients with SSI and 40 control patients without SSI were matched by type of surgery, wound class, ASA, sex and age. The direct and indirect costs to patients were obtained from patients and their carers, daily. The cost of drugs was confirmed with the pharmacy at the department. Results: The prevalence rate for SSI was 11% of the total 446 cases sampled between June and August 2017. On average patients with SSI who undertook hernia surgery paid approximately US 392 more than the matched controls without SSI. The least difference was recorded amongst patients who had thyroid surgery, a difference of US 42. The results show that for all surgical procedures, SSI patients report excess length of stay. The additional days range from 1 day for limb amputation, to 16 days for rectal surgery. Conclusions: In this study, patients with SSI experienced significant prolongation of hospitalisation and increased use of health care costs. In many cases, the indirect costs were much higher than direct costs. These findings support the need to implement preventative interventions for patients hospitalised for various surgical procedures at the Korle Bu Teaching Hospital.